2019
DOI: 10.1016/j.ijhcs.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Assisted pattern mining for discovering interactive behaviours on the web

Abstract: When the hypotheses about users' behaviour on interactive systems are unknown or weak, mining user interaction logs in a data-driven fashion can provide valuable insights. Yet, this process is full of challenges that prevent broader adoption of data-driven methods. We address these pitfalls by assisting user researchers in customising event sets, filtering the noisy outputs of the algorithms and providing tools for analysing such outputs in an exploratory fashion. This tooling facilitates the agile testing and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…While they are not widespread and their coverage is limited, tools such as WevQuery-PM [9] can lighten this burden.…”
Section: Discussionmentioning
confidence: 99%
“…While they are not widespread and their coverage is limited, tools such as WevQuery-PM [9] can lighten this burden.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to web user browsing behavior, a prominent source of data is web logs that store every website visitor's actions [160]. A recent study by Apaolaza and Vigo [161] addressed the challenges of mining web logs and proposed a set of functionalities into workflows that addresses these challenges. The study indicated that assisted pattern mining is perceived to be more useful and can produce more actionable knowledge for discovering interactive behaviors on the web.…”
Section: Web Miningmentioning
confidence: 99%
“…Data mining techniques are implemented to find useful patterns in large database such as MySQL and Oracle. It is the process that tries to discover patterns or techniques that can be applied in large dataset [2]. The main goal of data mining is to extract information from large dataset.…”
Section: Introductionmentioning
confidence: 99%